Propagation of Magnetic Fields from Electrical Domestic Appliances; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Orlova K. N. Kseniya Nikolaevna (2016, 2016)
Title screen